Hubungan Bimbingan Orangtua dengan Perilaku Sosial Kristiani Siswa di Lingkungan SMA N 3 Tarutung - Donna Irawati Sidauruk; Lince Sihombing; Wilson Simanjuntak; Albiner Siagian; Dame Taruli Simamora (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The purpose of this study was to determine the Positive and Significant Relationship Between Parental Guidance and Christian Social Behavior in the School Environment of Grade XI Students of SMA Negeri 3 Tarutung in the 2023/2024 Academic Year. This research method is a quantitative research method. The population of this study included all grade XI students of SMA Negeri 3 Tarutung who were Protestant Christians totaling 141 people, but only 36 people were determined as samples taken using purposive sampling techniques. Data were collected using a closed questionnaire of 42 items, 20 items for variable X and 22 items for variable Y. The results of data analysis showed that there was a positive and significant relationship between Parental Guidance and Christian Social Behavior of Students in the SMA Negeri 3 Tarutung Environment. This is proven by: 1) The positive relationship test obtained the value of rxy = 0.597> rtable = 0.329, thus it is concluded that there is a positive relationship between variable X and variable Y. 2) The significant relationship test obtained the value of tcount = 4.336> ttable = 2.042. Thus Ha which states that there is a positive and significant relationship between the Relationship between Parental Guidance and Christian Social Behavior of Students in the School Environment of Class XI SMA Negeri 3 Tarutung in the 2023/2024 Academic Year is accepted.